Meningkatkan Hasil Belajar Siswa Melalui Penggunaan Media Gambar pada Materi Kenampakan Alam di Kelas IV SDN Teluk Timbau - Sentia, Anis; Octavanny, Made Ayu Dwi; Rijal, Akmal (Jurnal Didaktika Pendidikan Dasar, 2024)
The learning process carried out by teachers in schools is still not careful and precise in choosing and using media. This research aims to describe the improvement in learning outcomes of 21 students using image media on Natural Appearances material in class IV at SDN Teluk Timbau. This research is classroom action research with a procedure consisting of four main components of classroom research, namely planning, action, observation and reflection in 2 cycles. The instruments used in this research were student activity observation sheets and tests. The data obtained in the research was analyzed using quantitative data analysis techniques and qualitative data. In pre-cycle activities, cycle I and cycle II there was an increase in activity and student learning outcomes which were then compared with the results of observations in previous learning. Learning outcomes in the pre-cycle with an average score of 62.29. In cycle I, a score of 74.00 was obtained and in cycle II, student learning outcomes increased to 82.38. Thus, the use of image media in natural appearance material in class IV SDN Teluk Timbau can increase student activity and learning outcomes. Learning outcomes in the precycle with an average score of 62.29. In cycle I obtained a value of 74.00 and in cycle II student learning outcomes increased to 82.38. Thus, the use of image media in natural appearance material in grade IV SDN Teluk Timbau can improve student activities and learning outcomes.